The Relationship Between Family Support and Dietary Adherence Among Mothers with Gestational Diabetes Mellitus - Jefrich nurpastikaningrum; Jiarti Kusbandiyah; Dinda Oktia Maghfiroh (Media Husada Journal of Midwifery Science, 2026)
Dietary compliance in mothers with Gestational Diabetes Mellitus (GDM) is an important aspect in controlling blood glucose levels during pregnancy to reduce the risk of complications. Family support plays an important role in improving dietary compliance in GDM mothers. This study aims to determine the relationship between family support and dietary compliance in GDM mothers at Dr. Saiful Anwar General Hospital, Malang City. This study used an observational analytical method with a cross-sectional design. Data collection was conducted from October to November 2024 at Dr. Saiful Anwar General Hospital, Malang City, with 96 respondents selected using non-probability sampling techniques according to inclusion and exclusion criteria. Data were collected through a family support questionnaire and a GDM mother's dietary compliance questionnaire. Data analysis used the Spearman rank test. Based on the results of the Spearman Rank test, a significant relationship was found between family support and GDM mother's dietary compliance (p-value = 0.000 p  0.05) with a very strong relationship strength (r = 0.998). Thus, H was rejected and H was accepted. It can be concluded that there is a significant relationship between family support and dietary compliance in mothers with gestational diabetes mellitus (GDM) at Dr. Saiful Anwar Regional General Hospital in Malang City. High levels of family support can increase maternal motivation and compliance in undergoing diet therapy.